«BRAIN DRAIN» FROM RUSSIA AS PROBLEM OF POLITICAL GOVERNANCE - A. A. Kazantsev; K. P. Borishpolets (Vestnik MGIMO-Universiteta)
When the status of the federal state at the international arena is in major defined by its scientific and technological potential, migration of the highly trained professional from or to Russia acquires a strategic status. The article is devoted to the consequences of the intellectual migration in Russia and proposals for optimization of the management policy at this direction. Authors regret that at this time in Russia the migration outflow of scientists and other specialists in quality and quantity figures substantially exceeds the inflow. This hinders plans on the modernization of the Russian economy and postpones refusal from extractive development model. Authors suggest expanding the governmental regulation of the intellectual migration in Russia by adopting special programs on the basis of the international experience. It shall be based on the principles of the differentiated and targeted approach to the intellectual migrants, effective monitoring, and effective feed-back relations when the decision are being implemented. The funding of the science also shall be increased both, by means of the target projects and exemptions to the science-driven business. The significance of these steps is high, particularly in the light of outflow of the Russian specialists abroad. If the positive tendencies will be supported by the active governmental policy and social-economic increase, in the mid-term perspective this may drive to turning point in the still negative situation with "brain drain" from Russia. It is worth to pay additional attention to the educational and scientific immigration to Russia as to an important offsetting factor if we do not want to lose this chance.